Application of 3D printed titanium mesh and digital guide plate in the repair of mandibular defects using double-layer folded fibula combined with simultaneous implantation - Li, Shangbo; Mi, Lian; Bai, Li; Liu, Zijian; Li, Li; Wu, Yupeng; Chen, Liqiang; Bai, Na; Sun, Jian; Liu, Yanshan (Frontiers in Bioengineering and Biotechnology, 2024)
Fibula transplantation plays an irreplaceable role in restoring the function and morphology of the defected mandible. However, the complex load-bearing environment of the mandible makes it urgent to accurately reconstruct the mandible, ensure the position of the condyle after surgery, and restore the patient’s occlusal function and contour. The intervention of digital design and three-dimensional (3D) printed titanium mesh provides a more efficient method and idea to solve this problem. Digital design guides the accurate positioning, osteotomy, and simultaneous implant placement during surgery, and 3D printed titanium mesh ensures stable condyle position after surgery, restoring good mandibular function. The double-layer folded fibula maintains the vertical height of the mandible and a good facial contour, and simultaneous implant placement can establish a good occlusal relationship. This study conducted a retrospective analysis of five patients with jaw defects who underwent digital fibula reconstruction over the past 3 years. It was found that the surgical protocol combining digital design, 3D printed intraoperative guides, 3D printed titanium mesh, free fibula flap, immediate implant, and occlusal reconstruction to repair jaw defects had more ideal facial appearance and biological function. It will provide a more reliable surgical protocol for clinical management of large mandibular defects.